2008
DOI: 10.1161/circheartfailure.108.768119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Significance of Delayed Enhancement in Hypertrophic Cardiomyopathy

Abstract: Background-Contrast-enhanced cardiovascular magnetic resonance with delayed enhancement (DE) can provide in vivo assessment of myocardial fibrosis. However, the clinical significance of DE in hypertrophic cardiomyopathy (HCM) remains unresolved. Methods and Results-Cine and cardiovascular magnetic resonance with DE were performed in 202 HCM patients (mean age, 42Ϯ17 years; 71% male), DE was compared with clinical and demographic variables, and patients were followed up for 681Ϯ249 days for adverse disease even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
210
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 277 publications
(236 citation statements)
references
References 52 publications
16
210
2
6
Order By: Relevance
“…Previous studies also showed that administration of isoproterenol could lead to cardiac hypertrophy (2,20). In fact, chronic stimulation of myocardial β-receptors could induce the process of hypertrophy (21,22). Our findings also showed that administration of diazepam 1 and 5 mg/kg significantly decreased the CMI of the isoproterenol-treated groups, which revealed the preventive role of diazepam against isoprpterenol-induced cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies also showed that administration of isoproterenol could lead to cardiac hypertrophy (2,20). In fact, chronic stimulation of myocardial β-receptors could induce the process of hypertrophy (21,22). Our findings also showed that administration of diazepam 1 and 5 mg/kg significantly decreased the CMI of the isoproterenol-treated groups, which revealed the preventive role of diazepam against isoprpterenol-induced cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 78%
“…This imbalance is caused by inadequate capillary density in relation to the increased myocardial mass and limitation of blood flow despite high oxygen demand of the myocardium (9,(33)(34)(35). Therefore, it could exacerbate the myocardial injury after ischemia (5,21,22). As it was expected, our findings showed the exacerbation of I/R injury in the isoproterenolinduced hypertrophied hearts.…”
Section: Discussionsupporting
confidence: 67%
“…The mean age of our population (56.4±17.0 years) was older than in most studies in the literature 5,11,12 and included few patients in the age-group most associated with sudden death (<35 years). Most were asymptomatic or mildly symptomatic, as in other published series.…”
Section: Discussionmentioning
confidence: 83%
“…Maron et al 12 reported a high prevalence, although not reaching statistical significance, of cardiovascular events during follow-up of 202 patients with HCM and LGE. By contrast, in a study of 220 asymptomatic or only mildly symptomatic HCM patients with a mean follow-up of three years, Bruder et al 15 showed that LGE was an independent predictor of cardiac death (hazard ratio [HR] 8.6; p=0.038), whereas the presence of one or two clinical risk factors did not reach statistical significance (HR 1.4; p=0.68).…”
Section: Discussionmentioning
confidence: 98%
“…İleriye dönük bazı çalışmalarda AKÖ gelişen veya uygun ICD şoklaması alan HKM hastalarında GGT'nin daha fazla görüldüğü belirlenmiştir (44). Hipertrofik kardiyomiyopatili hastaların yaklaşık %65'inde fibrozisin kanıtı olan GGT saptanması nedeniyle GGT'nin tek başına pozitif olmasının kardiyak olayları ön görmede iyi bir parametre olamayacağını düşünülmektedir (45). Eldeki mevcut veriler bu konuda yapılmış geniş çaplı ileriye dönük çalışma yapılmamış olmasından dolayı GGT'nin AKÖ açısından tek bağımsız risk faktörü olamayacağını belirtmektedir (45).…”
Section: Geç Gadolinyum Tutulumuunclassified